مفهوم المكان وعلاقته بعناصر السرد القصصي في ضوء النقد العربي المعاصر - محمود, عيد; عباس, فيروز (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
حظي المكان باهتمام الفلاسفة والنقاد قديماً وحديثاً , وتعدّدت المجالات التي درسته، وحاولت تقديم تعريفات له , وتحديد مفهومه . ويجـدُّ الباحث في مفهوم المكان في النقد الحديث تـنوّع مفهوماته عند النقاد , فهي خاضعة لرؤاهم النقدية على اختلاف توجهاتهم , لكنها لا تختلف على أهميتـه في إدراك جماليات القصة , بوصفـه عنصراً مهماً من عناصر السـرد القصصي, وهذا ما جعل هذه الدراسة تبحث في علاقته مع عناصر السـرد القصصي الأخرى للوصول إلى مفهوم ٍ واضح ٍ للمكان من خلال دراسة مجموعة من الآراء النقدية العربية المعاصرة , وتحليلها , ومحاولة فهم مضامينها , ومناقشتها , وكشف أبعادها , ودلالاتها . Place has captured the interest of philosophers and critics past and present. Many fields have studied it and tried to define it and specify its connotation. In modern criticism, the researcher finds various connotations in the concept of place in the writings of critics. According to their different interests, these connotations are subject to their critical visions. Nevertheless, they agree on its importance in recognizing the aesthetics of the story, since it is described as one of the important elements of the narrative. So this study deals with its relation to other elements of the narrative in order to get a clear picture of place. This is revealed by studying some contemporary Arabic critical opinions and analyzing them, attempting to understand and expose their contents and implications.